Laws of Work that Intersects with Non-Muslim Religious Rituals - Bahrun, Rahman (PT. Riset Press International, 2023)
This research aims to find out the laws that work in a place that intersects with other religious worship, whether the wages are halal or not halal. This study is a qualitative study with a descriptive analytical method. The results of the study show that the work is technical and does not necessarily show an attitude of glorifying non-Muslims in the context of their worship. In addition, aspects of usefulness and economic needs are also considered, as long as there are no elements that directly conflict with the principles of sharia.